Quantitative Real-Time PCR detection of TRPV1-4 gene expression in human leukocytes from healthy and hyposensitive subjects - Bachiocco Valeria; Marsili Letizia; Ceccarelli Ilaria; Panti Cristina; Zannolli Raffaella; Spinsanti Giacomo; Frati Francesco; Aloisi Anna (SAGE Publishing, 2008)
Abstract Background Besides functioning as chemosensors for a broad range of endogenous and synthetic ligands, transient receptor potential vanilloid (TRPV) 1-4 channels have also been related to capsaicin (TRPV1), pain, and thermal stimuli perception, and itching sensation (TRPV1-4). While the expression of the TRPV1-4 genes has been adequately proved in skin, sensory fibres and keratinocytes, less is known about TRPV3 and TRPV4 expression in human blood cells. Results To study the gene expression of TRPV1-4 genes in human leukocytes, a quantitative Real-Time PCR (qRT-PCR) method, based on the calculation of their relative expression, has been developed and validated. The four commonly used house-keeping genes (HKGs), β-Actin (Act-B), glyceraldehyde-3P-dehydrogenase (GAPDH), hypoxanthine ribosyltransferase (HPRT1), and cyclophilin B (hCyPB), were tested for the stability of their expression in several human leukocyte samples, and used in the normalization procedure to determine the mRNA levels of the TRPV 1-4 genes in 30 healthy subjects. cDNAs belonging to all the TRPV1-4 genes were detected in leukocytes but the genes appear to be expressed at different levels. Our analysis did not show significant sex differences in TRPV1-4 cDNA levels in the 30 healthy subjects. The same qRT-PCR assay was used to compare TRPV1-4 expression between healthy controls and patients hyposensitive to capsaicin, pain and thermal stimuli: an almost doubled up-regulation of the TRPV1 gene was found in the pathological subjects. Conclusion The qRT-PCR assay developed and tested in this study allowed us to determine the relative expression of TRPV1-4 genes in human leukocytes: TRPV3 is the least expressed gene of this pool, followed by TRPV4, TRPV1 and TRPV2. The comparison of TRPV1-4 gene expression between two groups of healthy and hyposensitive subjects highlighted the evident up-regulation of TRPV1, which was almost doubly expressed (1.9× normalized fold induction) in the latter group. All the four house-keeping genes tested in this work (Act-B, GAPDH, hCyPB, HPRT1) were classified as optimal controls and showed a constant expression in human leukocytes samples. We recommend the use of these genes in similar qRT-PCR studies on human blood cells.